Preparing for the Quit Day: Comparing Beliefs of Nondaily Versus Daily Young Adult Smokers as They Prepare for a Quit Attempt. Issue 6 (3rd September 2020) - Hoeppner, Bettina B; Hoeppner, Susanne S; Carlon, Hannah A; Abry, Alexandra; Darville, Audrey; Rohsenow, Damaris J
Abstract: Introduction: Most smoking cessation approaches are modeled on heavy daily smoking. With increasing prevalence of nondaily smoking, it may be necessary to modify these approaches for nondaily smokers. Aims: To provide information about beliefs and attitudes relevant to smoking cessation for nondaily smokers. Methods: Secondary analysis of two prospective studies on young adult smokers (18–24 years of age) provided brief advice to quit smoking. Measures include baseline levels of constructs relevant to smoking cessation counseling and perceived benefits of and barriers to smoking cessation. Results: Participants ( n = 40 nondaily, 122 daily smokers) were predominantly White (70% and 84%, respectively), gender-balanced (50% and 43% female), full-time college students (89% and 95%). At baseline, nondaily smokers reported lower levels of nicotine dependence ( p < .001; nondaily: Fagerström Test for Nicotine Dependence (FTND) = 0.8 ± 1.5, daily: FTND = 3.1 ± 1.9), lower urge to smoke ( p < .001), greater self-efficacy when facing external smoking stimuli ( p = .03), expecting to experience fewer positive effects (reduced negative affect, p = <.001, stimulation, p = .02), and valuing the importance of smoking effects less ( p s < .01) than daily smokers. During counseling, nondaily smokers generated both fewer benefits of cessation (Wald X 2 ( df = 1) = 4.91, p = .027) and fewer barriers (Wald X 2 ( df = 1) = 5.99, p =.014) than daily smokers. Withdrawal was not listed by nondaily smokers as a barrier ( p < .01). Conclusions: Constructs relevant to smoking cessation for daily smokers were less salient to young nondaily smokers, compared with moderately addicted young daily smokers, as indicated by responses to standardized scales and by the generation of fewer benefits and barriers in counseling. Interventions may need to find novel ways to engage nondaily smokers, particularly young adult, in smoking cessation efforts. Implications: This study is unique in eliciting benefits and barriers from nondaily smokers as they are about to make a quit attempt. This is a critically important point in time, as this is the point in time in which an action plan is formed and can be informed and enhanced by smoking cessation support. Our study further allowed direct comparison to daily smokers undergoing the same procedures, which allowed the identification of unique factors that may impact nondaily smokers in their quit attempt, which may guide intervention efforts. Use of a mixed method design further strengthen the rigor of this study.